Balanced Ethics Review A Guide for Institutional Review Board Members - Whitney, Simon N.; SpringerLink (Online service) (Cham : Springer International Publishing (Imprint), 2016)
As an Institutional Review Board (IRB) member, you must balance two interests. Your committee protects subjects and it permits the research that improves our health and lives. Balanced Ethics Review, drawing on basic principles of ethics and regulation, explains how to conduct this balancing task. It does not always provide the answer to knotty questions-that is your job-but it suggests a way of thinking, one that will help you reach morally-justified decisions that respect both subject welfare and our shared need for the fruits of research.
Title Page -- Dedication -- Preface -- Acknowledgements -- Chapter 1. Introduction -- 1.1 Overview -- 1.2 Ethics and the IRB -- 1.3 IRB Process -- 1.4 Evaluating Biomedical Research -- 1.5 Consent in Biomedical Research -- 1.6 The Social Sciences -- 1.7 Biomedical Research Topics -- 1.8 FDA and OHRP -- 1.9 The Future -- Chapter 2. Ethics and the IRB -- 2.1 Your Influential Position -- 2.2 Evidence -- 2.3 Scandal -- 2.4 Research Ethics -- 2.4.1 Two Ethical Principles -- 2.4.2 Two Ethical Goals -- 2.4.3 Goals into Practice -- 2.4.4 Today's Loss of Balance -- 2.4.5 It's Always about People -- 2.5 Ethical Goals and Regulatory Means -- 2.5.1 Principles of Regulation -- 2.5.2 Organization and Legal Framework -- 2.6 Your IRB Service -- 2.6.1 Compensation -- 2.6.2 Protection from Lawsuits -- 2.6.3 The Community Member -- 2.7 The Triumph of Ethics Review -- Chapter 3. IRB Process -- 3.1 Principles -- 3.1.1 Respectfulness -- 3.1.2 Transparency -- 3.1.3 Efficiency -- 3.1.4 Clarity -- 3.1.5 Accountability -- 3.1.6 Judiciousness -- 3.1.7 Rationality -- 3.1.8 Restraint -- 3.2 The Curse of Power -- 3.2.1 Scope of IRB Authority -- 3.2.2 Litigation Prevention -- 3.2.3 Beyond the Regulations -- Chapter 4. Evaluating Biomedical Research -- 4.1 The Objective IRB -- 4.1.1 Ramsey and the Scientist's Bias -- 4.1.2 Your Reasonable Understanding -- 4.2 Literature Reviews -- 4.2.1 Death at Johns Hopkins -- 4.2.2 Reviews by Investigators -- 4.2.3 Reviews by IRBs -- 4.3 Ethics and Science -- 4.3.1 Scientific Modifications -- 4.3.2 The Value of Research -- 4.3.3 Risk -- 4.4 Weighing Risks, Benefits, and Knowledge -- 4.4.1 Why You Should Protect Subjects -- 4.4.2 Why You Should Let Subjects Choose -- 4.4.3 The Conundrum -- 4.5 Approval Based on Risk and Benefit -- 4.5.1 Established Theories -- 4.5.2 Rajczi and Meyer: Let the Subjects Decide -- 4.6 Consent before Approval -- Chapter 5. Consent in Biomedical Research -- 5.1 Consent's Goals -- 5.2 Multisite Consent Forms -- 5.3 Presenting Risk and Benefit -- 5.4 Subject Understanding -- 5.4.1 Less is More -- 5.4.2 Ethical Considerations -- 5.5 Supervising Consent Form Writing -- 5.5.1 Helping the Investigator -- 5.5.2 Readability -- 5.5.3 Format -- 5.6 Editing the Consent Form -- Chapter 6. The Social Sciences -- 6.1 The Value of Dissent -- 6.2 The Social Impact of Research -- 6.3 Freedom of Speech -- 6.4 Psychology -- 6.4.1 Deception -- 6.4.2 Threats to Self-Esteem -- 6.5 Surveys and Interviews -- 6.5.1 Risk and Benefit -- 6.5.2 Modifications -- 6.6 Field Research -- 6.6.1 Risk -- 6.6.2 The Sociologists' Dispute -- 6.7 Racial Discrimination -- Chapter 7. Biomedical Research Topics -- 7.1 Archival Research -- 7.1.1 Cancer of the Vagina -- 7.1.2 Regulatory Oversight -- 7.1.3 Ethical Considerations -- 7.1.4 The Common Rule -- 7.1.5 HIPAA -- 7.2 The Learning Health Care System -- 7.2.1 Integrating Research and Clinical Care -- 7.2.2 Ethical Considerations -- 7.2.3 Your IRB's Role -- 7.3 Randomized Controlled Trials -- 7.3.1 Risks Inside and Outside of a Trial -- 7.3.2 Nonphysical Risks -- 7.4 Comparative Effectiveness Trials -- 7.4.1 Identifying the Better Treatment -- 7.4.2 Faden's Bold Ethical Proposal -- 7.4. Waiver of Consent in Special Circumstances -- 7.5 Justice -- 7.5.1 Unjust Burdens -- 7.5.2 The Governmental Pursuit of Justice -- 7.5.3 The Private Pursuit of Justice -- 7.6 The Vulnerable -- 7.6.1 Regulatory Overprotection -- 7.6.2 Fighting Health Disparities -- 7.7 Paying Subjects -- 7.7.1 Respecting Subject Choice -- 7.7.2 Coercion -- 7.7.3 Setting a Cap on Wages -- 7.8 Emergency Research -- 7.8.1 Criteria for Approval -- 7.8.2 Ethical Considerations -- 7.9 Phase 1 Cancer Trials -- Chapter 8. FDA and OHRP -- 8.1 Agencies under Pressure -- 8.2 Your IRB and the Agencies -- 8.2.1 Balancing Three Goals -- 8.2.2 When Regulations Trump Ethics -- 8.2.3 The Successful IRB -- 8.2.4 Things Can Go Wrong -- 8.3 Pushing Back against Federal Pressure -- 8.3.1 The Agency -- 8.3.2 The Funder -- 8.3.3 The Media -- 8.3.4 The Courts -- 8.4 Risk and your IRB -- Chapter 9. The Future -- 9.1 Evidence -- 9.2 Reform -- 9.3 The Challenge -- References -- Index.
Keywords: Anthropology; Epidemiology